1990
DOI: 10.1111/j.1432-1033.1990.tb19406.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabel‐transfer cross‐linking demonstrates that protein 4.1 binds to the N‐terminal region of β spectrin and to actin in binary interactions

Abstract: Erythrocyte protein 4.1 plays a major role in stabilizing the spectrin-actin junction of the erythrocyte membrane skeleton. The particular sites on spectrin responsible for the binding of actin and protein 4.1 have not been specifically defined, although the general region of the 'tail' end, opposite the self-association site, has been deduced by electron microscopy. Using a photoactivatable, radiolabel-transfer cross-linker, l-[N-(2-hydroxy-5-azidobenzoyl)-2-aminoethyl]-4-(N-hydroxysuccinimidyl)-succinate, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 66 publications
2
17
1
Order By: Relevance
“…In agreement, a mutant of Caspr lacking its intracellular domain was not retained properly on the axolemma at the paranodal junction (Gollan et al, 2002). Caspr interacts with protein 4.1B (Gollan et al, 2002;Denisenko-Nehrbass et al, 2003), and 4.1 family members bind to the N terminus of ␤-spectrins (Becker et al, 1990(Becker et al, , 1993. ␤II spectrin and ␣II spectrin interact as antiparallel heterodimers, and these heterodimers associate further to form heterotetramers.…”
Section: The Paranodal Protein Complexmentioning
confidence: 65%
“…In agreement, a mutant of Caspr lacking its intracellular domain was not retained properly on the axolemma at the paranodal junction (Gollan et al, 2002). Caspr interacts with protein 4.1B (Gollan et al, 2002;Denisenko-Nehrbass et al, 2003), and 4.1 family members bind to the N terminus of ␤-spectrins (Becker et al, 1990(Becker et al, , 1993. ␤II spectrin and ␣II spectrin interact as antiparallel heterodimers, and these heterodimers associate further to form heterotetramers.…”
Section: The Paranodal Protein Complexmentioning
confidence: 65%
“…We had also previously shown that the binding site for protein 4.1 was located within the NH2-terminal region of (3 spectrin before the beginning of the spectrin repeat structure ( 12). We therefore decided to amplify this region of the :3 spectrin cDNA.…”
Section: Resultsmentioning
confidence: 99%
“…Binary interaction between spectrin and actin is characterized by a weak binding (K a ϳ 5 ϫ 10 ) (3,5). While the interaction between protein 4.1 and F-actin was initially found to be weak (5), more recent studies suggest a cooperative mechanism for this interaction (6). 1 In contrast, protein 4.1 binds strongly to spectrin (K a ranging from ϳ0.5 to 86 ϫ 10 6 M Ϫ1 ) (7)(8)(9)(10).…”
Section: ϫ2mentioning
confidence: 99%